Plants used for hemorrhoid treatment in elazi? central district - Çakilcio?lu, U.; T?rko?lu, I. (International Society for Horticultural Science, 2009)
This study examined plants used to treat hemorrhoid disease by the folk in the central district of Elazi? city. In the study, one-to-one survey was conducted with 300 individual's with hemorrhoid, who went to private hospitals for examination and pharmacies to buy drugs between February 2005 and November 2006. The participant's were asked which parts of the plants they used and how they prepared these, and their answers were recorded. The plants used were collected duly, converted into herbarium materials, and scientifically designated. Plants that were found to be used commonly included Urtica dioica L., Bellis perennis L., Allium sativum L., Morus nigra L., Juniperus oxycedrus L., Allium cepa L., Vitis vinifera L., and Ajuga chamaepitys L. Schreber. Data from the survey forms were evaluated using SPSS 12.0 statistical software. Chi-square values were calculated, and their significance was examined. A significant correlation was established between participant's consumption status of the plants used in hemorrhoid treatment and their duration of residence, educational status and familiarity status.
Keywords: Alternative crop; Folk drugs; Medicinal plant; Phytotherapy